The Long-term effect of social disasters on stock market participation - Cai, Yang; Chen, Shuo; Li, Dongxu (Journal of Corporate Finance, 2025)
This study examines the long-term impact of social disaster experiences on household finance. Using the Cultural Revolution in China, the country’s most pronounced sociopolitical turmoil that completely disrupted millions of people’s lives, we show that households are more likely to participate in the stock market if their eldest member was more exposed to the turmoil. The results remain robust to alternative historical events, socioeconomic factors, and household characteristics. Survey results suggest that the more exposed individuals invest in the stock market because they perceive stocks as low risk rather than have altered risk preferences or trust in stock markets.